Kinetic studies on pancreatic lipase inhibition: article / Muhammad Hafiz Abdul Basir - Abdul Basir, Muhammad Hafiz; Najwa, Miradatul (2019)
Obesity and its associated diseases and coronary heart diseases are a major challenge for our society. An important target for the treatment of obesity includes the development inhibitors of nutrient digestion and absorption. Pancreatic lipase is the enzyme responsible for digestion and absorption of triglycerides, being its inhibition one of the widest studied methods used to determine the potential activity of natural products to inhibit dietary fat absorption. Decrease of energy intake from dietary fat through inhibition of this enzyme may be an excellent strategy to prevent and treat obesity.The inhibitory activity on pancreatic lipase enzyme of Lawsonia Inermis or henna leaves was evaluated using the spectrophotometer to get the concentration. Inhibition of pancreatic lipase are found by using the michelis menten equation, lineweaverburk, hanees wolf plot and eadie hofstee plot. The enzyme kinetics were obtained with different concentration of substrate (cooking oil) and gallic acid, quercetin, pancreatic lipase and buffer were the constant. Then the result was plotted to get the correct mode of inhibition.